2019
DOI: 10.1126/scisignal.aav4663
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of Ca 2+ influx by ORAI channels mediates enamel mineralization

Abstract: Store-operated Ca2+ entry (SOCE) channels are highly selective Ca2+ channels activated by the endoplasmic reticulum (ER) sensors STIM1 and STIM2. Their direct interaction with the pore-forming plasma membrane ORAI proteins (ORAI1, ORAI2, and ORAI3) leads to sustained Ca2+ fluxes that are critical for many cellular functions. Mutations in the human ORAI1 gene result in immunodeficiency, anhidrotic ectodermal dysplasia, and enamel defects. In our investigation of the role of ORAI proteins in enamel, we identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 69 publications
(127 reference statements)
9
63
0
Order By: Relevance
“…When store depletion was prevented or only endogenous STIM1 was present at the channel, no I CRAC was observed. In line with previous studies [15,61], the expression of one or more Orai3 subunit(s) within these channels result in a significant reduction of I CRAC that was also observed in endogenous systems [15][16][17][18]23,24]. In concatenated channels, expression of two or more Orai3 subunits resulted in 2-APB-induced outward currents in STIM1-dependent and store-independent 2-APB-activated channels.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…When store depletion was prevented or only endogenous STIM1 was present at the channel, no I CRAC was observed. In line with previous studies [15,61], the expression of one or more Orai3 subunit(s) within these channels result in a significant reduction of I CRAC that was also observed in endogenous systems [15][16][17][18]23,24]. In concatenated channels, expression of two or more Orai3 subunits resulted in 2-APB-induced outward currents in STIM1-dependent and store-independent 2-APB-activated channels.…”
Section: Discussionsupporting
confidence: 88%
“…Endogenous heteromeric SOCE channels have been reported in different cell types [15][16][17][18][19][20][21][22]. Orai3 may be a negative modulator as, upon knockdown of Orai3, SOCE can be increased [15][16][17][18]23,24]. In contrast, in other studies, SOCE is decreased upon knockout of Orai3, indicating a role as a positive modulator of SOCE [25][26][27][28].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Since ER Ca 2+ levels are determined by the relative balance between Ca 2+ leak by leak channels and refilling by SERCA, un-altered resting ER Ca 2+ content together with a weaker ER Ca 2+ leakage would imply a less SERCA pumping activity. We thus directly measured refilling of ER Ca 2+ store with R-CEPIA1er and a protocol adapted from one previous report [35]. In permeabilized, ER Ca 2+ store depleted RIPK cells, addition of 1 mM ATP and 100 nM Ca 2+ would enable the refilling of Ca 2+ into ER by SERCA, as indicated by increases in R-CEPIA1er signals ( Figure 2C).…”
Section: Overexpression Of Ip 3 R1 or Ip 3 R3 Could Rescue The Impairmentioning
confidence: 90%
“…In developing rodent teeth, it has been shown that PMCA pumps and their encoding genes [42] as well as Orai and Stim proteins and their encoding genes [43][44][45][46][47] are expressed in ameloblasts, the enamel-forming cells, and genetic studies in humans and mice have revealed a critical role for Orai and Stim proteins for proper enamel formation [43,[46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%